The Effect Of Language Learning Strategy Instruction On The Academic Achievement Of Below Average Vocational College Efl Learners In China - Jiao, Chen (2024)
Language learning strategy has been acknowledged as a significant technique for English learning. Some effective strategies can make learners accomplish the questions by themselves and feel powerful to regulate their English language learning process. However, there are few studies related to the LLS instruction of below-average EFL learners, and there are more problems that need to be explored. Several problems are reported: 1) learners lack of knowledge on how to learn English effectively; 2) the numbers of EFL below-average college learners are increasing. Consequently, the purpose of this study was to 1) investigate the frequency and preference of LLS used by below-average learners; 2) determine whether LLS instruction is effective in increasing below-average EFL learners’ LSU and EAA; 3) explore the efficient LLS instruction model for below-average EFL learners. Specifically, the study distributed SILL questionnaires to 442 Chinese EFL college learners to investigate the frequency and preference of LLS use. Intervention programme also conducted for 40 Chinese EFL learners to explore the effect of LLS instruction on the LSU and EAA of below-average learners. The study employed three instruments: (1) Strategy Inventory for Language Learning (SILL); Tests of English academic achievement (EAA), namely, (2) Test-4 (CET-4) and (3) College English Final Exam (CEFE), which were conducted for pre-test and post-test of the intervention program. From a qualitative perspective, the study applied outline of semi-structured interviews (OSIs). Overall, the study made analysis and triangulation of the data from SILL, CET-4, CEFE, and SOIs common themes referring to the LLS instruction, LSU, and EAA, and finally developed the efficient LLS instruction model based on 20 interviewees’ report on LLS instruction.